A case study on tail brush induced loads upon segmental lining - S.K. Yadav; L. Han; G.L. Ye (Lowland Technology International, 2019)
Damage to the tunnel segmental lining induced by the construction loads has become an important issue in recent years. In this study, in-situ monitoring was carried out to measure the pressure on the lining of a large cross-river shield tunnel along Yangtze River (diameter D=11.36m) with a small overburden (0.7D) in silty sandy ground. PAD type earth pressure gauges were used to measure the tail brush pressure on the lining. The time history and the distribution of pressures on the lining during tunnel construction were obtained. It showed that the tail brush pressure had a considerable effect on the segments while the shield machine was passing through. Non-uniform tail brush pressures caused cracking and water leakages in the reinforced concrete segments.